How to Design Tax Policy in Fragile States - Mansour, Mario (IMF How To Notes; How-To Note ;, 2019)
The purpose of this note is to provide a framework for improving tax policy design in fragile and conflict-affected states, which face political and institutional constraints. This note begins with an overview of experiences in revenue mobilization in fragile states, including relative to other country groups-in particular, nonfragile states and formerly fragile states; that is, countries that exited fragility during the period under study. A discussion follows of how the principles of tax policy design should be applied in fragile states, particularly the relative importance of the revenue objective vis-a-vis other objectives, such as equity and efficiency. The two sections that follow provide guidance on tax policy design in the emergency and consolidation phases, respectively, and discuss how governments can use tax policy to transition from one phase to another, eventually overcoming fragility. The note concludes with key lessons and a set of guiding principles for tax reform in fragile states.